Relationship between eliciting doses and the severity of allergic reactions to food. Issue 3 (28th June 2023) - Yanagida, Noriyuki; Sato, Sakura; Ebisawa, Motohiro
Abstract : Purpose of review: Food allergies with low thresholds are associated with frequent accidental allergic reactions. Severe reactions attributable to accidental ingestion often result in a poor quality of life. Nevertheless, no evidence of a relationship between a low threshold dose and the severity of symptoms exists. Therefore, we evaluated recent data regarding the threshold of food allergies based on the oral food challenge (OFC). We also proposed a stepwise OFC method to identify threshold and consumable doses. Recent findings: A higher specific IgE level and a history of food-induced anaphylaxis were related to low threshold doses and severe reactions during the OFC. In addition, a low threshold dose was not directly correlated with severe reactions. Performing a stepwise OFC may help safely clarify consumable doses and prevent the complete avoidance of allergy-causing foods. Summary: Severe food allergies with high specific IgE levels are associated with lower thresholds and more severe reactions. However, the threshold is not directly related to the severity of food-induced allergic symptoms. Identifying a well tolerated consumable dose using a stepwise OFC may help manage food allergies.